2010
DOI: 10.1016/j.jss.2009.11.123
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Lethal Septic Shock without Fluid Resuscitation in a Rodent Model

Abstract: Background-We have recently demonstrated that treatment with suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor, before a lethal dose of lipopolysaccharide (LPS) improves survival in mice. The purpose of the present study was to determine whether SAHA treatment would attenuate LPS-induced shock and improve survival when given postinsult in a rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…This result would be the logical consequence of the use of an HDAC-6 inhibitor, such as vorinostat, in a LPSinduced septic shock model. A recent report (55), showed that administration of vorinostat (50 mg/kg intraperitoneally) after a lethal dose of LPS significantly improved long-term survival and reduced the expression of TNFα and IL-6. The authors also observed that vorinostat reduced the increased expression of MyD88 caused by LPS administration and postulated that this may be the direct consequence of the decreased expression of MyD88-associated proinflammatory genes.…”
Section: Molecular Mechanisms Of Action Of Hdaci's Related To Antiinfmentioning
confidence: 99%
“…This result would be the logical consequence of the use of an HDAC-6 inhibitor, such as vorinostat, in a LPSinduced septic shock model. A recent report (55), showed that administration of vorinostat (50 mg/kg intraperitoneally) after a lethal dose of LPS significantly improved long-term survival and reduced the expression of TNFα and IL-6. The authors also observed that vorinostat reduced the increased expression of MyD88 caused by LPS administration and postulated that this may be the direct consequence of the decreased expression of MyD88-associated proinflammatory genes.…”
Section: Molecular Mechanisms Of Action Of Hdaci's Related To Antiinfmentioning
confidence: 99%
“…Genetic deficiency of MyD88 partially protected mice from the lethal effects of polymicrobial sepsis, and hyperinflammatory response to sepsis was strongly attenuated in the absence of MyD88 21 . Our team has previously demonstrated that SAHA can reduce MyD88 expression at both gene and protein levels after LPS insult in the lung tissue, suggesting that inhibition of TLR4-MyD88-dependent pathway could be one explanation for the anti-inflammatory effects of SAHA 9 . Currently, it remains elusive as to how acetylation affects expression of MyD88.…”
Section: Discussionmentioning
confidence: 97%
“…However, it remains unknown whether treatment with SAHA could improve survival from lethal septic shock. Our lab was the first to demonstrate that administration of SAHA improved survival in a rodent model of lipopolysaccharide (LPS)-induced lethal endotoxemia 9,10 . In this model, it decreased acute lung injury, and rapidly modulated several key genes involved in inflammation, with an attenuation of inflammatory mediators derived from both cellular and humoral arms of the innate immune system 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Our research team has demonstrated that both hemorrhage and sepsis can lead to protein hypoacetylation, whereas therapeutically targeting the alterations with HDACIs induces acetylation of histone and non-histone proteins, and is protective against lethal insults, such as hemorrhagic shock, traumatic brain injuries, endotoxemic shock, and severe sepsis. [15][16][17][18] In humans and mice, the 18 HDAC enzymes are grouped into four classes: classical HDACs, including class I, II and IV, are Zn 2+ dependent, while the classes III sirtuins act through a NAD + -dependent mechanism. HDAC6 belongs to class IIb HDAC and is unique in that it is a cytoplasmic microtubule-associated enzyme.…”
Section: Discussionmentioning
confidence: 99%